Host Gall Size and Temperature Influence Voltinism in an Exotic Parasitoid - Aguirrebengoa, Martin; Wong, María Eva; Boyero, Juan Ramón; Quinto, Javier (Frontiers in Ecology and Evolution, 2022)
Insect phenology is highly temperature-dependent. Higher temperatures can lead to earlier emergence and lengthening of the active period, which enable many insect groups to complete more generations. Studies on the effects of climate change on insect populations are providing concerning evidence supporting this relationship. These kind of shifts in phenology and voltinism also occur in agricultural and forest insect pests and their natural enemies, with potential implications for biological control. The consequences derived from changing temperature regimes on tritrophic interactions remain poorly studied, particularly in gall-inducing insects and their parasitoids. Here we detail the occurrence of bivoltinism in the exotic parasitoid Torymus sinensis, previously categorized as univoltine, a widely introduced species to fight against the invasive Asian chestnut gall wasp Dryocosmus kuriphilus wherever this pest spread. This plasticity in voltinism has been observed in the southernmost European distribution of D. kuriphilus, and appears to be mediated by both temperature and gall traits, namely size or the number of gall chambers. Bivoltinism was most common at annual mean temperatures around 13.5 °C and in galls with more chambers. Through this work, we intend to unravel the factors behind this phenomenon and discern the possible consequences on host-parasitoid interactions.